Assessing intracellular and extracellular antibiotic resistance gene proliferation during the treatment of municipal wastewater by an anaerobic membrane bioreactor - ElKhoury, Charbel (2022)
As water scarcity is emerging as a great threat nowadays, water reuse is a critical component of the solution. Among many tested wastewater treatment technologies, anaerobic membrane bioreactors (AnMBRs) have proven their unique treatment capabilities for producing high quality effluents and recovering energy. The removal of emerging microbial contaminants from wastewater, such as antibiotic resistance genes (ARGs) and uncultivable pathogens, has not been extensively studied for AnMBRs during treatment of real (non-synthetic) municipal wastewaters. Hence, this research aimed to assess the ability of AnMBRs to achieve removal of both extracellular and intracellular ARGs (eARGs and iARGs, respectively), as the two can proliferate through vastly different means in wastewater treatment environments. The experiment consisted of a lab-scale AnMBR treating a local wastewater source under various conditions. The experiment was designed to compare ultrafiltration (UF) and microfiltration (MF) membrane effluent profiles at different transmembrane flow rates and different membrane fouling levels. The phases of operation included: a transition from synthetic to real wastewater, stepwise increases in transmembrane flux, and post membrane replacement to assess the effect of membrane fouling. It was observed that higher effluent abundances of iARGs were related to higher transmembrane flux rates while eARGs were not directly affected by flux. eARGs were also more abundant overall in the effluent, which appeared to be a direct result of corresponding influent wastewater profiles. Moreover, it was found that the fouled UF membrane was more effective at removing certain genes (such as sul1 and intI1) as compared to an unfouled UF membrane. This study provides new insights regarding ARG dynamics in AnMBR effluents by elucidating the effect of operating different membrane types, maintaining membrane biofilms, and controling transmembrane flux rates on the nature of ARGs released into the permeate.